Deubiquitinases at the interplay between hematopoietic stem cell aging and myelodysplastic transformation - Citterio, Elisabetta; Ronchi, Antonella Ellena (FEBS letters, 2024)
Hematopoietic stem cells (HSC) maintain blood production throughout life. Nevertheless, HSC functionality deteriorates upon physiological aging leading to the increased prevalence of haematological diseases and hematopoietic malignancies in the elderly. Deubiquitinating enzymes (DUBs) by reverting protein ubiquitination ensure proper proteostasis, a key process in HSC maintenance and fitness. Hematopoietic stem cell (HSC) function declines during aging, leading to a higher risk of hematopoietic malignancies. By reverting protein ubiquitination, deubiquitinating enzymes (DUBs) ensure protein homeostasis, a key process in HSC maintenance. Here, we discuss how alterations in DUBs function exacerbate HSC aging, predisposing them to myelodysplastic syndrome and leukaemia. The potential of DUBs as therapeutic targets is highlighted.